Leaving the teaching profession : examining the role of social support, engagement and emotional intelligence in teachers' intentions to quit - Mérida-López, Sergio, (Colegio Oficial de Psicólogos de Madrid, 2020)
The study aimed to test mediator and moderator factors in the relationship between workplace social support (i.e., perceived support from colleagues and supervisors) and intentions to quit in a sample of teaching professionals. Specifically, utilizing job-demands-resources theory to focus on social support, we examined whether work engagement mediated the relationship between workplace social support and intentions to quit. Moreover, the potential moderator role of emotional intelligence in the proposed model was tested. The study sample comprised 1,297 teaching professionals (64.8% females) working as preschool, primary, and secondary teachers in several centers in eastern and southern Spain. The main results demonstrated that work engagement totally mediated the relationship between social support from colleagues/supervisors and intentions to quit. The findings showed that teachers levels of emotional intelligence significantly moderated the indirect paths between perceived support from colleagues/supervisors and intentions to quit. Teachers with the lowest levels of work engagement reported low support from colleagues or supervisors, together with low emotional intelligence. Similarly, highest intentions to quit was reported by those teachers reporting low work engagement and low emotional intelligence. Finally, we discuss the relevance of these findings for basic and applied research seeking to retain a more engaged teaching force.